2013
DOI: 10.1007/s11011-013-9420-4
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal baseline brain activity in patients with HBV-related cirrhosis without overt hepatic encephalopathy revealed by resting-state functional MRI

Abstract: Neurocognitive dysfunction of varying degrees is common in patients with hepatitis B virus-related cirrhosis (HBV-RC) without overt hepatic encephalopathy (OHE). However, the neurobiological mechanisms underlying these dysfunctions are not well understood. We sought to identify changes in the neural activity of patients with HBV-RC without OHE in the resting state by using the amplitude of low-frequency fluctuation (ALFF) method and to determine whether these changes were related to impaired cognition. Resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Using cortical thickness, surface area and lGI, this study aims to perform a comprehensive analysis on the cortical morphometry of a relatively homogeneous sample of patients with HBV-RC without OHE (HBV-RC-NOHE) vs. matched healthy controls. Based on previous studies (Montoliu et al, 2012 ; Lv et al, 2013a , b ), we hypothesized that patients with HBV-RC-NOHE would exhibit cortical thickness reduction in multiple brain regions including the parietal lobe, the temporal lobe and the occipital lobe. In addition, given that many studies have reported intensive white matter abnormalities (Kumar et al, 2008 ; Chen et al, 2012 ; Qi et al, 2013 ) and the hypothesis that cortical gyrification was mainly caused by the tension of the underlying white matter connectivity (Van Essen, 1997 ; Herculano-Houzel et al, 2010 ), cortical gyrification alterations are also expected in patients with HBV-RC-NOHE.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using cortical thickness, surface area and lGI, this study aims to perform a comprehensive analysis on the cortical morphometry of a relatively homogeneous sample of patients with HBV-RC without OHE (HBV-RC-NOHE) vs. matched healthy controls. Based on previous studies (Montoliu et al, 2012 ; Lv et al, 2013a , b ), we hypothesized that patients with HBV-RC-NOHE would exhibit cortical thickness reduction in multiple brain regions including the parietal lobe, the temporal lobe and the occipital lobe. In addition, given that many studies have reported intensive white matter abnormalities (Kumar et al, 2008 ; Chen et al, 2012 ; Qi et al, 2013 ) and the hypothesis that cortical gyrification was mainly caused by the tension of the underlying white matter connectivity (Van Essen, 1997 ; Herculano-Houzel et al, 2010 ), cortical gyrification alterations are also expected in patients with HBV-RC-NOHE.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, cirrhotic patients without OHE do not present recognizable clinical neuropsychiatric symptoms but associate with a varying degree of cognitive deficits mainly in visual perception, visuo-constructive abilities, fine motor performance, attention and memory (Lv et al, 2013a ), which could be quantitatively measured by the psychometric hepatic encephalopathy score (PHES; Weissenborn, 2008 ). Using resting-state functional magnetic resonance imaging (fMRI) data, several studies have been conducted to explore the neural correlates of the cognitive deficits in cirrhotic patients without OHE (Lv et al, 2013a , b ; Chen et al, 2014 ). Nevertheless, little effort has been made to investigate the cortical integrity in cirrhotic patients without OHE.…”
Section: Introductionmentioning
confidence: 99%
“…Recent resting-state functional magnetic resonance imaging (fMRI) studies also emphasize the importance of aberrant brain intrinsic activity in the pathogenesis of MHE. For example, Chen and colleagues [ 12 , 13 ] report MHE-related changes in brain regional intrinsic neuronal activity by measuring the amplitude of low-frequency fluctuations (ALFF) in fMRI signals. Similarly, regional homogeneity (ReHo), an index reflecting the local synchrony of intrinsic brain activity, is also shown to be altered in MHE patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to HBV effects on liver, patients with CHB may exhibit depression and reduction in their HRQoL. HBV infection could influence the central nervous system and cause cognitive dysfunction in many ways 23,24. However, the mechanism between behavioral disorders that negatively affect HRQoL and HBV chronic infection is still unknown.…”
Section: Discussionmentioning
confidence: 99%